EFFECTS OF IMPLEMENTING MODULAR CONTAINER STRUCTURE TOWARDS THE ROOM AND CORRIDOR QUALITY IN CHARA HOTEL - Nathania Nadia ; Laurentia Carissa (Riset Arsitektur (RISA), 2019)
Abstract- Containers have a lifetime, so afterwards abandoned. The use of used containers as buildings has grown and become popular in some countries. Containers have fixed length, width and height. The use of containers as a hotel function requires adjustment of size and material. This research will analyze how far the fixed container structure is used in the Chara Hotel, adapters of fixed containers with the space requirements in them and the effect of container material on human psychology.Research is reviewed in quantitative (size) and qualitative (psychological effects). The research will be done by looking how far the container structure is used in the building. Analysis of how closely the relationship between the structure of the container and the rigid frame with the bedroom and corridor architecture is in terms of room size and space quality.The size of the contianer dimension can be put to good use as a function of the bedroom. Structural containers and rigid frame structures is a frame structures and architectural structures. The length and height of the corridor are good, the width of the corridor is less wide. The function of the space of the container structure and the rigid frame to space is good because the structure does not impede function and circulation. Key Words: container structure, rigid frame structure, space quantity, space quality